2018
DOI: 10.1371/journal.pone.0198679
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of suicide in New South Wales men with prostate cancer: Analysis of linked population-wide data

Abstract: BackgroundAn elevated risk of suicide after a diagnosis of prostate cancer has been reported previously in the USA and Sweden. We aimed to identify whether prostate cancer survivors resident in New South Wales Australia are at higher risk of suicide and if so, who is most at risk.MethodsData were obtained from the New South Wales (NSW) Cancer Registry for all men diagnosed with prostate cancer in NSW during 1997 to 2007. These were linked by the Centre for Health Record Linkage (CHeReL) to Australian Bureau of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Overdiagnosis is important because of the associated iatrogenic harms and costs . Harms include the psychosocial impact of unnecessary cancer diagnoses, such as the increased suicide risk for men after being diagnosed with prostate cancer . Cancer treatments such as surgery, radiotherapy, endocrine therapy, and chemotherapy can cause physical harm, but the risks are considered acceptable if diagnosis is appropriate.…”
mentioning
confidence: 99%
“…Overdiagnosis is important because of the associated iatrogenic harms and costs . Harms include the psychosocial impact of unnecessary cancer diagnoses, such as the increased suicide risk for men after being diagnosed with prostate cancer . Cancer treatments such as surgery, radiotherapy, endocrine therapy, and chemotherapy can cause physical harm, but the risks are considered acceptable if diagnosis is appropriate.…”
mentioning
confidence: 99%
“…20 This new study confirms these findings in a well-characterised surgical population closely tracked more than 24 months and further supports the need for life course to be considered in men's risk profiles for poorer survivorship outcomes. $40 001 to $60 000 70 (27) $60 001 to $80 000 48 (19) $80 001 + 40 (15) Unwilling to answer/Don't know 12 (5) Comorbid condition, n (%) Myocardial infarction 21 (7) Heart failure 13 ( Prospective longitudinal studies are now emerging to describe how this distress evolves over time. More than 1.1 million men are diagnosed with prostate cancer each year worldwide, and most of them will be long-term survivors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis reported that at diagnosis of prostate cancer and treatment, 15% to 27% of men experience anxiety and 15% to 18% report depression . In addition, men have an increased risk of suicide after prostate cancer by comparison with controls, with the first year after diagnosis a period of heightened risk . It is therefore advised that after the diagnosis of prostate cancer and regularly through treatment and surveillance, men are screened regularly for distress and referred for evidence‐based psychosocial intervention when indicated .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Survival is high with 90.6% of men living 10 years after diagnosis (AIHW, ), however many men and their partners experience decrements in quality of life and well‐being. Specifically, the survivorship experience of men with prostate cancer may be accompanied by physical symptoms including urinary, bowel and sexual dysfunction, poor quality of life, increased psychological distress and a heightened risk of suicide (Chambers et al, ; Holland, Watson, & Dunn, ; Smith et al, , ). For partners and carers, psychosocial burden can also be considerable and in several studies partners have reported greater psychological distress than prostate cancer survivors (Cliff & MacDonagh, ; Couper et al, ; Eton, Lepore, & Helgeson, ).…”
Section: Introductionmentioning
confidence: 99%